2021
DOI: 10.2147/ott.s310164
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Zinc Finger Protein 395 Contributes to the Pathogenesis of Chondrosarcoma

Abstract: Introduction The transcription factor zinc finger protein 395 (ZNF395) is involved in several cellular responses and tumorigenesis. However, the potential role and clinical significance of ZNF395 in chondrosarcoma are not well investigated. This study determines the expression profile, prognostic value and biological function of ZNF395 in human chondrosarcoma. Methods The mRNA and protein expressions of ZNF395 in fresh chondrosarcomas and the matched adjacent non-tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(85 reference statements)
0
2
0
Order By: Relevance
“… 5 , 6 PBF is a DNA‐binding transcription factor that is overexpressed in human cancers, including glioblastoma, kidney cancer, osteosarcoma, Ewing sarcoma, and neuroblastoma, and plays an oncogenic role in carcinogenesis. 7 We previously reported that PBF protein is highly expressed in 92% of osteosarcoma biopsy specimens. Furthermore, patients with PBF‐positive osteosarcoma had a significantly worse prognosis than those with negative PBF expression.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“… 5 , 6 PBF is a DNA‐binding transcription factor that is overexpressed in human cancers, including glioblastoma, kidney cancer, osteosarcoma, Ewing sarcoma, and neuroblastoma, and plays an oncogenic role in carcinogenesis. 7 We previously reported that PBF protein is highly expressed in 92% of osteosarcoma biopsy specimens. Furthermore, patients with PBF‐positive osteosarcoma had a significantly worse prognosis than those with negative PBF expression.…”
Section: Introductionmentioning
confidence: 95%
“…We previously identified papillomavirus binding factor (PBF) as an osteosarcoma antigen recognized by an autologous cytotoxic T lymphocyte (CTL) clone 5,6 . PBF is a DNA‐binding transcription factor that is overexpressed in human cancers, including glioblastoma, kidney cancer, osteosarcoma, Ewing sarcoma, and neuroblastoma, and plays an oncogenic role in carcinogenesis 7 . We previously reported that PBF protein is highly expressed in 92% of osteosarcoma biopsy specimens.…”
Section: Introductionmentioning
confidence: 99%